Analisis Efektivitas Program Pendidikan Agama Kristen terhadap Kualitas Pembelajaran di Kelas - Dyulius Thomas Bilo; Anggi Laurencia (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2025)
This study aims to evaluate the effectiveness of the Christian Religious Education (CRE) program in enhancing the quality of classroom learning through a qualitative approach. The main focus of this research includes the planning, implementation, and evaluation of the CRE program, as well as its contribution to improving students' understanding of Christian values, character formation, and active participation in the learning process. Data were collected through direct classroom observation, in-depth interviews with teachers and students, and document analysis of learning tools and the curriculum used. The findings indicate that a contextually designed CRE program that aligns with students' needs can create a more reflective and participatory learning environment. Teachers with both pedagogical and spiritual competence play a crucial role in effectively communicating Christian values through teaching methods, exemplary behavior, and daily interactions with students. Furthermore, the integration of learning content with real-life situations encourages students to internalize Christian teachings in their attitudes and behaviors, both in school and in their daily lives. However, the study also identified several challenges, such as limited instructional time, a lack of value-based learning media development, and difficulties in motivating students with weak spiritual backgrounds. Therefore, strengthening teacher capacity, developing more creative teaching methods, and institutional support from schools are essential to optimize the role of CRE in fostering a holistic and transformative learning experience.